Efektivitas Penyuluhan dengan Media Video dan Booklet dalam Meningkatkan Pengetahuan Ibu Tentang Upaya Kesehatan Gigi dan Mulut Balita - Dini Rahayu; Oktavia Dewi; Agus Alamsyah; Nurlisis Nurlisis; Irwan Muryanto (Jurnal Kesehatan Komunitas, 2021)
A mother's knowledge is an important factor in the health of toddlers because a mother has an effect on the child's education process from an early age. Knowledge, attitude, and action of a mother toward maintaining oral and dental health will determine the oral and dental health status of the toddler. The Initial survey conducted by 80% of mothers in Hariosari Village has low knowledge on the oral and dental health of toddlers. This study aimed to determine which media of education was more effective in increasing mothers' knowledge of toddler oral and dental health efforts. This type of research is quantitative with a Quasi Experimental-Nonequivalent Control Design. The sample in this study amounted to 54 obtained using the purposive sampling technique. The instruments used in the study were the questioner pre-test and post-test knowledge.Â The analysis used was the Wilcoxon test, Kruskal-Wallis test, and Man Whitney. The result of the research from the Wilcoxon test showed that there was a difference in the knowledge of the mother before and after being given the video media and booklet treatment (p-value <0 05). The Kruskal-Wallis test showed a difference in knowledge improvement between the video group, booklet, and control (p-value <0.05). Through the Mann-Whitney test, there was no significant difference between the video group and booklet (p-value> 0.05). This research concludes that video media and booklet media are equally effective in increasing a mother's knowledge of the oral and dental health effort of a toddler.Â